Degradation Process and Mechanism of Dissolved Organic Matter in Microplastics under Ultraviolet Light - Barouta, Apostolos; Orosa, Jorge (Journal of Green Energy and Environmental Engineering, 2026)
Microplastic dissolved organic matter not only endangers human health, causes damage to the immune barrier and affects agricultural production, but also interacts with environmental components such as heavy metals and antibiotics, exacerbating environmental pollution. In this study, the degradation process and transformation mechanism of five microplastic dissolved organic matter (MPDOM) under ultraviolet irradiation were studied by ultraviolet-visible spectrophotometry, three-dimensional fluorescence combined with parallel factor analysis, Fourier transform infrared spectroscopy and Fourier transform ion cyclotron resonance mass spectrometry. The results showed that PSDOM and PETDOM had the best degradation effect under UV irradiation, and the degradation effect of PPDOM was poor. The analysis of UV spectra and three-dimensional fluorescence spectra showed that PSDOM and PETDOM had a high degree of aromaticity and humification, and contained more unsaturated aromatic structures (benzene ring, conjugated double bond, etc.) and fluorescent components (humus, etc.). The above structures and components were preferentially degraded under ultraviolet light. In addition, the mass difference network analysis of MPDOM before and after degradation was carried out to explore the main transformation pathways involved in the degradation process. The results showed that the five MPDOM all underwent a series of reactions (oxygen addition reaction, decarboxylation reaction and dealkylation reaction, etc.) dominated by oxygen addition (+O, +O2, and +O3, etc.) to degrade unsaturated aromatic structures and humus into small molecules under UV irradiation. In addition, the precursor compounds of PPDOM also contain some sulfur-containing compounds, which are mainly degraded by desulfonation reaction. This study reveals the degradation characteristics and molecular transformation mechanism of five microplastics dissolved organic matter under ultraviolet light irradiation, which is helpful to further understand the harm of microplastics dissolved organic matter and its degradation products to the environment.